Ідеологема «українська мова» в сучасному російському науковому дискурсі (на матеріалі стенограми Круглого столу) - Космеда, Тетяна; Kosmeda, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті йдеться про своєрідну вербалізацію ідеологеми «українська мова», що простежено під час наукової комунікативної діяльності, яка відбувалася в МДУ ім. М. В. Ломоносова в межах Круглого столу «Русский язык в условиях языковой и культурной полифонии». Дослідницьким матеріалом є стенограма цього заходу, де репрезентоване живе наукове мовлення. У ході аналізу простежено надмірну афективну ідеологізовану «псевдонаукову» комунікацію, що ґрунтується на вираженні й відповідному омовленні сукупності почуттів, оцінок, емоцій, еґо-думок та «ідеологічних міфів», скерованих на приниження України, української мови, українців; вербалізовано зневагу, насмішку, іронію і сарказм. The article focuses on the analysis of the verbalization peculiarities of the ideologeme «the Ukrainian Language» which have been identified in the course of exploring the scientific communicative activities at a Round Table Discussion held at M. V. Lomonosov Moscow State University. The topic of the Round Table Discussion was «The Russian Language under Conditions of Language and Cultural Polyphony». The verbatim records of the Round Table Discussion has become the material of the research, which present live scientific speech of the Russian scientists recorded in the verbatim reports. The research offers insights into the specific affective, idealogized «pseudoscientific communication». This «pseudoscientific communication» is greatly dependent on the expression and verbalization of feelings, emotions, estimations, ego-thoughts, «ideological myths» aimed at the humiliation of Ukraine, the Ukrainian language, the Ukrainians as the nation, the verbalization of disrespect, mockery and sarcasm. The scientists’ speech is characterized by the violation of a scientific argumentation, etiquette, correctness. All these things do not comply with the scientific style norms, but represent the ideological rhetoric, appealing to «their» own history, while the history of the Ukrainian nation has been misrepresented and falsified. The allusion has been created on the very fact that there was no russification, that there were no prohibitions of the Ukrainian language, culture, and the Ukrainian state as a whole. The author draws the conclusion that, in fact this ideology has been cultivated for centuries and penetrated even the scientific discussions.
The Ideologeme «Ukrainian language» in Modern Russian Scientific Discourse (Case Study of the Roundtable Verbatim Records)
Keywords: російський науковий дискурс; живе мовлення; наукова комунікація; ідеологема; українська мова; Russian scientific discourse; live speech; scientific communication; ideologem; the Ukrainian language